Exploring how Grade 11 Biology teachers mediate learning of osmosis when using easily accessible resources in the Oshikoto Region, Namibia - Nangolo, Rosalia Ndawapeka (Rhodes University, Faculty of Education, Department of Education, 2019)
Exploring the use easily accessible resources to carry out the hands-on practical activities to science learning has become one of the significant aspects in the educational research, particularly in science education. It could be deduced from the literature that hands-on practical activities are useful, enjoyable and foster conceptual understanding. The National Curriculum for Basic Education advocates empowering teachers to be knowledgeable on use of hands-on practical activities to produce learners who are scientifically equipped. Yet, the performance of the learners in Science and Mathematics continues to be worrisome and has not been improving over years as reported in TIMSS reports. For instance, the Namibian Examiners' Reports have repeatedly reported that Biology is one of the subjects that are poorly performed. Essentially, the section on osmosis has been identified as one of the scientific concepts that is problematic to learners. In my view, in order for learners to understand osmosis and its associated concepts, there is a need to strengthen the use of hands-on practical activities. It is recognized that this is something that is lacking in most rural Namibian schools especially where laboratory resources are scarce. It is against this background that the goal of this study was to explore how Grade 11 Biology teachers mediate learning of osmosis when using easily accessible resources. This study is underpinned by an interpretive paradigm. Within the interpretive paradigm, a qualitative case study approach was employed to obtain in-depth understanding on how Biology teachers mediate learning. This study was conducted in two conveniently selected secondary schools in the Oshikoto region, which I could easily access. It focused on four Grade 11 Biology teachers. Data were generated through semi-structured interviews, workshop discussions, lesson observation and stimulated interviews. Vygotsky's (1978) socio-cultural theory was used as a lens to analyse my data. The findings from semi-structured interviews revealed that teachers demonstrated positive attitudes towards teaching of osmosis using easily accessible resources. However, challenges regarding inadequate materials that hinder the teaching and learning process were registered. Another finding of this study was that teachers used a variety of mediation tools such as prior and local knowledge, language and easily accessible resources to enhance learning. The study thus recommends that, if teachers are exposed to numerous professional development platforms that include the use of easily accessible resources might improve their pedagogical approaches.
Keywords: Biology -- Study and teaching (Secondary) -- Namibia; Osmosis -- Study and teaching (Secondary) -- Namibia; Ethnobiology -- Namibia